Studi Komparasi Dimensi Parenting Style terhadap Prokrastinasi Akademik Siswa SMA "X" - Singlaire Theola Adhatia Hendrawan; Marissa Chitra Sulastra (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2022)
This study aims to determine the contribution of the parenting style dimension to the academic procrastination of 'X' high school students. Respondents in this study were 224 people. This research is a correlation study that uses a linear regression analysis method. The parenting style dimension questionnaire used is a scale of parenting style (Gafoor, 2014) which has been translated by researchers and carried out readability tests by experts. The questionnaire contains 38 items of statements with a validity coefficient of 0.38 - 0.89. Reliability test results are 0.94 for the responsiveness dimension and 0.95 for the demandingness dimension. The academic procrastination questionnaire used was a questionnaire compiled by Mercy (2019) and had a total of 24 statements. The validity of this measuring instrument ranges from 0.01 - 0.72 and reliability is 0.84. The result of this study is that there is no significant contribution from the parenting style dimension to the academic procrastination of 'X' high school students. The researcher's suggestion is, further research can be carried out by measuring the contribution of other factors that can affect academic procrastination in high school students. Keywords: Parenting Style Dimension; Academic Procrastintio; High School Student